Impact of Alcohol on HIV Disease Pathogenesis, Comorbidities and Aging: Integrating Preclinical and Clinical Findings. - Molina, Patricia E.; Simon, Liz; Amedee, Angela M.; Welsh, David A.; Ferguson, Tekeda F. (Alcohol & Alcoholism, 2018)
Alcohol's multisystemic effects impact HIV disease pathogenesis and increase the risk for comorbidities in persons living with HIV (PLWH). The increased number of aging PLWH increases the potential for alcohol to enhance the risk for comorbidities. Integration of epidemiological, preclinical and translational studies provide an overarching view of the impact of heavy alcohol consumption on HIV risk, pathogenesis, treatment and burden of disease. The combined insult of HIV infection, heavy alcohol consumption and toxic effects of antiretroviral therapy in aging PLWH poses a public health challenge through increased disease burden that also impacts quality of life and increases health care costs. Herein we provide a brief overview of current knowledge on alcohol's impact on HIV disease pathogenesis, with focus on aging PLWH. Short Summary: Effective combined antiretroviral therapy regimens have extended survival of persons living with HIV (PLWH). Heavy alcohol consumption is common in PLWH. This overview integrates evidence from clinical and preclinical research to identify salient alcohol-related mechanisms and comorbidities contributing to disease pathogenesis and accelerated aging and senescence in PLWH.